THE IMPLEMENTATION OF READERS’ THEATER IN TEACHING READING COMPREHENSION AT THE THIRD YEAR STUDENTS OF SMP MAHA PUTRA TELLO MAKASSAR - Erwin Hafid; Ratu Yunita Sekar (Langkawi: Journal of The Association for Arabic and English, 2016)
This research discussed about the implementation of Readers’ Theater in teaching reading comprehension. The objective of the research was to find out whether or not the Readers’ Theater affects on the students’ reading comprehension. This research applied pre-experimental method consisting of eight meetings. The students were given a pre-test, then they were treated by applying Readers’ Theater, and finally, they were given a post-test. The data were collected through reading test. The result of the data analysis showed that there was difference between the students’ score in pre-test and post-test. It was proved by the mean score in post-test (6.58) was higher than the mean score in the pre-test (5.5). Moreover, the result of test of significant analysis indicated that the implementation of Readers’ Theater affected the students’ reading comprehension.